Peran Impulsive Buying Saat Live Streaming Pada Masa Pandemi Covid-19 (Studi Kasus E-Commerce Shopee) - Fitryani Fitryani; Aditya Surya Nanda; Erwan Aristyanto (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2021)
A This study aims to determine the behavior patterns of people who incidentally are e-commerce consumers who are users of goods or services. Public shopping activities are supported by the increasing volume of types of products that are needed by the community during the Covid-19 pandemic which requires people to stay at home so as to encourage impulsive buying behavior, especially to overcome boredom. This study uses a descriptive qualitative method which aims to answer the problem of how the impact of impulse buying on the purchasing power of the community in the midst of the Covid-19 pandemic, the impact of live streaming on buying interest in the midst of the Covid-19 pandemic, on e-commerce shopee, how is the impact of impulse buying. The results show that impulsive buying behavior occurs when users do live streaming so that it has an impact on the tendency of consumers to buy because they remember what they have thought, impulsive buyers make buyers more wasteful, especially in buying goods, even though in reality the product is not needed by consumers, spending money for temporary interests and looking for pleasure in shopping are the reasons why consumers do impulse buyingKeyword      : ecommerce, live streaming, impulsive buying, pandemic